1984
DOI: 10.1021/jm00374a010
|View full text |Cite
|
Sign up to set email alerts
|

.beta.-Lapachone: synthesis of derivatives and activities in tumor models

Abstract: In order to find a 3,4-dihydro-2H-naphtho[1,2-b]pyran-5,6-dione more potent than the naturally occurring 2,2-dimethyl derivative [beta-lapachone (10a)], we synthesized a series of analogous compounds with modifications at position 2 of the pyran ring or at positions 8 and 9 of the benzene ring. Of the compounds tested in vitro for inhibition of RNA-dependent DNA polymerase and in mice infected with Rauscher leukemia, all retained good enzyme activity. Inhibition of the reverse transcriptase activity of the 2,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 0 publications
1
61
0
Order By: Relevance
“…␤-Lapachone is a quinone-containing compound originally obtained from the lapacho tree in South America [5]. Previous studies found that ␤-lapachone, an effective chemotherapeutic and radio-sensitizing agent, selectively induces apoptosis in a number of human breast and prostate cancer cell lines that is dependent on expression level of NAD(P)H:quinine oxidoreductase 1 (NQO1) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…␤-Lapachone is a quinone-containing compound originally obtained from the lapacho tree in South America [5]. Previous studies found that ␤-lapachone, an effective chemotherapeutic and radio-sensitizing agent, selectively induces apoptosis in a number of human breast and prostate cancer cell lines that is dependent on expression level of NAD(P)H:quinine oxidoreductase 1 (NQO1) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…3,4-Dihydro-2,2-dimethyl-2H-naphthol [1,2-b]pyran-5,6-dione (␤-lapachone) is found in Pau d'arco trees (Tabebuia impetiginosa) and possesses antitumor activity against S-180 leukemic cells, Yoshida sarcoma cells, sarcoma 180 cells, and Walker 256 carcinoma cells in early studies (Docampo et al, 1979;Schaffner-Sabba et al, 1984;Chau et al, 1998). ARQ 501 is a fully synthetic ␤-lapachone and has been identified as a potent activator of E2F1.…”
mentioning
confidence: 99%
“…l3-Lapachone, which is isolated from plant extracts (9), has a variety of pharmacological effects (10,11). Toxicity data in humans are not available for (3-lapachone; it is well tolerated in mice at <40 mg/kg given i.v.…”
mentioning
confidence: 99%
“…(unpublished data). The maximum tolerated dose is about 1250 mg/kg given orally in mouse and chicken (10). Curcumin, the major active component of the food flavor tumeric, has been eaten, up to 100 mg/day, for a thousand years, and pharmacological studies demonstrate its very low toxicity.…”
mentioning
confidence: 99%